Dynamics of Political Entrepreneurship among the Elites in Post-Colonial Zimbabwe - Tarugarira, Gilbert (Department of Political Sciences , University of Pretoria, 2022)
The political arena is now abounding with people who either live ‘off ’ or ‘for’ politics. The ferocious competition for people’s votes is akin to economic competition, and as this study submits, the politicians are just like business people. Both productive and predatory profi t opportunities have pervaded the Zimbabwean political arena, where politics is a type of business. Political positions have afforded some people access to economic resources, making politics the quickest way to untold and unending riches. As a result, the political landscape has invited abuse of power, thereby decimating not the physical being but the entire moral fi bre of the nation. This study shows how Zimbabwean political leaders have become the primary controllers and distributors of power and resources with the capacity to penetrate society politically and secure their hegemony. Reference is made to politicians belonging to the ruling party Zimbabwe African National Union-Patriotic Front (ZANU-PF) and the opposition Movement for Democratic Change (MDC), where politicians from either party have exhibited, though not uniformly, patterns of misconduct characteristic of political entrepreneurship. This paper applies the entrepreneur’s theory to political behaviour to identify political entrepreneurs and analytically distinguish them from other government agents.